Brave The Wild River : the untold story of two women who mapped the botany of the Grand Canyon - Sevigny, Melissa L., 1986- (New York, NY : W.W. Norton & Company, 2024)
Traces the forty-three-day journey of pioneering botanists Elzada Clover and Lois Jotter, who in the summer of 1938, set out to catalogue the plant life of the Grand Canyon. Recounts the obstacles they faced from misogynistic doubters and the Colorado River's dangerous rapids, their successful endeavor to painstakingly identify all the plant species in the canyon, and the trip's legacy for future conservation efforts in the region.
Prologue: stranded -- On the borders of precipices -- Have you seen that river? -- A mighty poor place for women -- There goes the Mexican hat! -- A beautiful pea-green boat -- Delayed -- Hell, yes! What river? -- Paradise -- A most unusual and hazardous means -- A hundred personalities -- Lonely for the river -- Heaven as I go along -- Legendary -- Epilogue: a woman's place.
new book 2025 spring.
Includes bibliographical references and index.
Publishers Weekly Starred
10-12.
Keywords: Clover, Elzada U., -- 1897-1980 -- Travel -- Arizona -- Grand Canyon; Jotter Cutter, Lois, -- 1914-2013 -- Travel -- Arizona -- Grand Canyon; Nevills, Norman D., -- 1908-1949 -- Travel -- Arizona -- Grand Canyon; Women travelers -- Arizona -- Grand Canyon -- History -- 20th century; Botanists -- Biography -- Arizona -- Grand Canyon; Botany -- History -- Arizona -- Grand Canyon -- 20th century; Plant collecting -- Arizona -- Grand Canyon -- History -- 20th century; Scientific expeditions -- Arizona -- Grand Canyon -- History -- 20th century; Grand Canyon (Ariz.) -- Discovery and exploration; Colorado River (Colo.-Mexico) -- Discovery and exploration; Grand Canyon (Ariz.) -- Description and travel